2020
DOI: 10.1057/s41291-019-00064-4
|View full text |Cite|
|
Sign up to set email alerts
|

Interpretation and integration of “creating shared value” in Asia: implications for strategy research and practice

Abstract: “Creating shared value” (CSV) appears on contemporary business agendas. But despite empirical evidence concerning its popularity, serious questions about the logic of CSV are raised by scholars. This paper focuses on CSV in the Asian context. Using in-depth interviews with key informants from Japan, Korea, and India, we employ a strategy-as-practice approach and develop propositions related to CSV in Asia. We identify three characteristics of Asian business practices that shape CSV in Asia: a survival sense, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 60 publications
0
15
0
1
Order By: Relevance
“…Firstly, it is strictly economic in nature and does not consider, for example, moral and social factors (Beschorner, 2014; Tencati et al., 2020). For instance, research has found a strong ethical stance to be a determinant for CSV in Asia (Kim et al., 2019), but research on the matter is still at too early a stage to be included in a comprehensive framework.…”
Section: The Three Main Research Streams On Csvmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, it is strictly economic in nature and does not consider, for example, moral and social factors (Beschorner, 2014; Tencati et al., 2020). For instance, research has found a strong ethical stance to be a determinant for CSV in Asia (Kim et al., 2019), but research on the matter is still at too early a stage to be included in a comprehensive framework.…”
Section: The Three Main Research Streams On Csvmentioning
confidence: 99%
“…Besides the aforementioned factors, some scholars suggest that CSV adoption can be motivated by a sense of survival, a strong ethical stance and a willingness to do good in society (Kim et al., 2019). However, others raise doubts as to the potential of CSV projects ‘to stimulate sustainable development processes without radically changing entrepreneurs’ cognitive frames from growth first to humanizing the business’ (Giuliani et al., 2020, p. 1).…”
Section: The Three Main Research Streams On Csvmentioning
confidence: 99%
“…Especially in the East Asian institutional environment, where the influence of Confucianism is strong, people tend to react negatively to the idea of an economic system that encourages maximization of profits, since profit for one person implies loss for someone else (Allinson, 2011). Therefore, “show me ethical stewardship” is more critical for business survival in Asia than “show me the money” (Chen et al., 2018; Kim et al., 2020; McGinn & Zoltners, 2015; Wu & Wokutch, 2015). One CSR expert in Korea opined:
In the recent impeachment case of ex‐President Park Geun‐hye, you can see that it was an indictment of not only the leader’s incompetence but also of her immorality.
…”
Section: Resultsmentioning
confidence: 99%
“…According to the concept of Creating Shared Value (CSV) (Lombardo and Cabiddu, 2017; Porter and Kramer, 2019; Ranjan and Read, 2016), organizations driven by shared values promote win-win thinking, with shared values becoming a crucial factor in fostering positive outcomes related to specific investment, qualification of capability, and firm performance (Arena et al. , 2021; Bacq and Aguilera, 2022; Kim et al. , 2020; Lombardo and Cabiddu, 2017; Marcos-Cuevas et al.…”
Section: Theoretical Model and Research Hypothesesmentioning
confidence: 99%